Studi Optimasi Pola Tanam Daerah Irigasi Gong Gang Kecamatan Parang Kabupaten Magetan - Ernawan Setyono; safik Mucharom (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2016)
Along with the increasing population growth, the need for food also increased. To meet that need for optimization studies of the factors that influence spatial patterns of planting in order to increase the volume of food production. Determination of the cropping pattern that will be used after the first known dependable flow and water requirements. Through the design cropping pattern is expected cropping intensity can be enhanced and existing water sources can be used optimally. linear programming used in this optimization study using QM for Windows 4 software. The most optimal results from the optimization that has been done is an alternative was began on November cropping patterns : rice-palawija-sugarcane season crops beginning 1st week of November, profits amounted to Rp 106.729.700.000 to the area that can be cultivated for the planting season I: Rice = 1990 ha, palawija = 307 ha sugarcane = 89 ha, planting season II: Rice = 1990 ha, palawija = 307 ha sugarcane = 89 ha, and planting season III: Rice = 258,2753 ha Palawija = 2038,725 ha, sugarcane = 89 ha